Graphene in rubber formulations: a comprehensive review and performance optimization insights - Leong, Y. L.; Lim, H. N.; Ibrahim, I. (Royal Society of Chemistry (RSC), 2023)
Graphene is widely incorporated into rubber matrices to enhance mechanical, electrical, and thermal properties in nanocomposites. However, its hydrophobicity and lack of functionalities cause agglomeration, impacting nanocomposite properties. Intense agitation techniques like mechanical blending, grinding, and sonication modify graphene and disrupt π-π interactions between sheets. Hybrid fillers, such as carbon nanotubes, metals, nanocellulose, and nanocrystals, enhance graphene's dispersibility and create new value in nanocomposites. Graphene's exceptional properties make it applicable in the medical, electronics, and tire industries. Optimizing graphene incorporation is crucial to exploit its benefits. Response surface methodology (RSM) optimizes graphene nanocomposites effectively and efficiently, surpassing traditional methods. The review discusses recent advancements in graphene modification, hybridization, and applications in rubber products. Furthermore, RSM utilization for optimizing graphene-rubber nanocomposites is explored. The paper concludes with future prospects for graphene in rubber formulations.